Zika virus: Molecular responses and tissue tropism in the mammalian host - Shaily, Sangya; Upadhya, Archana (Reviews in medical virology, 2019)
Summary Zika virus (ZIKV) outbreaks have raised alarm because of reports of congenital Zika virus syndrome in infants. The virus is also known to cause the debilitating Guillain–Barré syndrome in adults. As a result, extensive research has been carried out on the virus over the past few years. To study the molecular responses of viral infectivity in mammals, in vitro two‐dimensional and three‐dimensional cellular models have been employed. The in vivo models of mouse, pig, chicken, and nonhuman primates are primarily used to investigate the teratogenicity of the virus, to study effects of the virus on specific tissues, and to study the systemic effects of a proposed antiviral agent. The virus exhibits wide tissue tropism in the mammalian host. The major host tissues of viral persistence and propagation are neural tissue, ocular tissue, testicular tissue and placental tissue. An understanding of the function of viral components, viral replication cycle, and the molecular responses elicited in the host tissues is imperative for designing antiviral treatment strategies and for development of vaccines. This review provides an update on ZIKV research models and mammalian host responses with respect to ZIKV tissue infection.